Pulmonary resection undertaken with a provisional but unsubstantiated diagnosis of bronchial carcinoma - le Roux, B. T. (1972)
Over a 15-year period when frozen-section examination was not regularly available, 918 patients with peripheral pulmonary lesions (the routine preliminary investigation of which did not provide a diagnosis) were managed aggressively by a diagnostic pulmonary resection which, before 1954, was in some patients of the magnitude of pneumonectomy, but after that date was never more extensive than lobectomy and often no more than segmental resection. In 756 patients (82%) the lesion was shown to be a primary or metastatic pulmonary tumour and in 162 patients (18%) the lesion was a chronic inflammation or a pulmonary infarct. The commonest pulmonary lesion judged so closely to mimic pulmonary carcinoma that management by exploratory thoracotomy and diagnostic pulmonary resection was mandatory was pulmonary tuberculosis (82 patients); other lesions encountered were cavitated (8 patients) and non-cavitated (16 patients) pneumonias; pulmonary gummata (2 patients); progressive massive fibrosis (4 patients); and a pulmonary infarct (5 patients). It is estimated that in perhaps 60 patients (6·5% of the total) with nontumorous lesions the pulmonary resection undertaken was needless, or of unnecessary magnitude, and some of these resections might have been avoided if skilled interpretation of frozen sections had constantly been available.